Perajang Rempah Otomatis Untuk Mengembangkan Usaha Minuman Sehat Berbasis UMKM di Malang - Widiyanti; Nurmalasari, Riana; Ramadhani, Viola Malta; Romadin, Achmad (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
MSMEs in Malang that are engaged in the food and beverage industry still carry out the process of chopping ingredients using simple equipment. Most MSMEs chop ingredients using a blender or manually using a knife. This condition clearly causes culinary production on a MSME scale not maximized. It is necessary to develop technology that can help MSMEs to improve the quality and quantity of their production. Based on the results of community service activities by developing automatic spice chopping technology for healthy drink businesses, MSMEs can produce much more varied products. This is because the role of technology makes the production process much faster and can be easy to innovate. Technology functions as an important element in the development of MSMEs, encouraging innovation, increasing operational efficiency, and expanding market access. Although challenges still exist in the form of limited resources and skills, targeted support from the government and educational institutions can empower MSMEs to utilize the potential of technology to the maximum. As the business landscape continues to evolve, the ability of MSMEs to adapt and innovate through technology will be very important for their sustainability and growth.